APLIKASI DATA EKSTERNAL DAN INTERNAL PADA PROGRAM BEASISWA AKTIVIS SALMAN - Firda Dwi Anjani; Soni Akhmad Nulhaqim; Gigin Ginanjar Kamil Basar (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2022)
Abstract. Rumah amal salman is a human service organization where its service activities are in the form of collecting, managing, and distributing ZISWAF (Zakat, Infaq, Sadaqah, and Waqf). The distribution of zakat is carried out in the form of programs, one of which is the salman activist scholarship program. This article aims to describe the application of external and internal data on management information systems in the salman activist scholarship program in rumah amal salman. The description begins with a description of management information systems in human service organization, and is followed by a discussion of the application of external and internal data in the management information system for decision making in the salman activist scholarship program.. Consideration of internal and external data input is important in order to produce comprehensive, accurate, and useful information for the benefit of the organization. The research method in this article uses a qualitative approach. Data collection was carried out by interviews, literature study, and documentation study. The results show that rumah amal salman considers the application of external and internal data on the management information system in making decisions to support the sustainability of the salman activst scholarship program. In conclusion, the researcher also gives advice on the need to optimize the application of political data by increasing cooperation with the government, the community, and other organizations to expand the range of services. This is reinforced by the potential for an salman scholarship activist program in the form of social project activities that have an impact on the community.Keyword: human service organization; management information system; external data; internal data.Abstrak. Rumah amal salman merupakan organisasi pelayanan manusia dimana kegiatan pelayanannya berupa penghimpunan, pengelolaan, dan pendistribusian dana ZISWAF (Zakat, Infaq, Shadaqah, dan Wakaf). Pendistribusian zakat dilakukan dalam bentuk program, salah satunya adalah program beasiswa aktivis. Artikel ini bertujuan untuk mendeskripsikan aplikasi data eksternal dan internal pada sistem informasi manajemen dalam program beasiswa aktivis di rumah amal salman. Pendeskripsian diawali dengan penjabaran mengenai sistem informasi manajemen dalam organisasi pelayanan manusia, serta dilanjutkan dengan pembahasan mengenai aplikasi data eksternal dan internal pada sistem informasi manajemen rumah amal salman dalam program beasiswa aktivis. Pertimbangan aplikasi data eksternal dan internal merupakan hal penting dalam rangka menghasilkan informasi yang komprehensif, tepat, serta dapat bermanfaat bagi kepentingan organisasi. Metode penelitian pada artikel ini menggunakan pendekatan kualitatif. Pengumpulan data dilakukan dengan wawancara, studi literatur, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa rumah amal salman mempertimbangkan aplikasi data eksternal dan internal pada sistem informasi manajemen dalam rangka pengambilan keputusan untuk mendukung keberlanjutan program beasiswa aktivis salman. Sebagai kesimpulan, peneliti juga memberikan saran perlunya optimalisasi aplikasi data politik dengan meningkatkan kerjasama baik dengan pemerintah, masyarakat, maupun organisasi lainnya untuk memperluas jangkauan pelayanan. Hal ini diperkuat dengan adanya potensi program beasiswa aktivis berupa kegiatan proyek sosial yang berdampak bagi masyarakat.Kata Kunci: organisasi pelayanan manusia; sistem informasi manajemen; data eksternal; data internal.